Krung Thēp Mahā Nakh̨ōn : kānwikhr̨o ch̄œng phūmisāt kānl̄ưaktang rawāng pī Ph̨ō. S̨ō. 2500-2519 = Greater Bangkok : an analysis in electoral geography, 1957-1976 - Supannee Chalothon (Khrōngkān Sưksā Nayōbāi Sāthārana, Samākhom Sangkhomsāt h̄æng Prathēt Thai, 1986)
Paper presented to seminar on politics and elections in Thailand organized by Social Science Association of Thailand and Konrad Adenauer Foundation, held in Bangkok, Thailand, July 13, 1986.